2015
DOI: 10.18632/oncotarget.3929
|View full text |Cite
|
Sign up to set email alerts
|

Rapatar, a nanoformulation of rapamycin, decreases chemically-induced benign prostate hyperplasia in rats

Abstract: Benign prostatic hyperplasia (BPH) is the most common age-related disease in men. Here we tested the efficacy of Rapatar, a micellar nanoformulation of rapamycin, in two rat models of BPH: testosterone-induced and sulpiride-induced hyperplasia in ventral lobes and lateral/dorsal lobes, respectively. We found that Rapatar prevented hypertrophic and hyperplastic abnormalities and degenerative alterations in both BPH models. Rapatar normalized weight of the lateral lobes in sulpiride-induced BPH, the most relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…To nominate potential subtype specific therapeutic options, we utilized the Connectivity Map 40, 41 analysis ( Figure 4A and Table S13), which uses transcriptional expression data to probe relationships between diseases, cell physiology, and therapeutics. Strikingly, we found 50% of nominated compounds in BPH-A subgroup were related to inhibition of mTOR signaling ( Figure 4B), and the subgroup enrichment of mTOR signaling was validated in two independent cohorts ( Figure 4C), consistent with prior isolated reports in model systems 42,43,44 . To interrogate the potential effect of mTOR treatment on the prostate, we examined prostate size on cross-sectional imaging in patients taking mTOR inhibitors.…”
Section: Resultssupporting
confidence: 86%
“…To nominate potential subtype specific therapeutic options, we utilized the Connectivity Map 40, 41 analysis ( Figure 4A and Table S13), which uses transcriptional expression data to probe relationships between diseases, cell physiology, and therapeutics. Strikingly, we found 50% of nominated compounds in BPH-A subgroup were related to inhibition of mTOR signaling ( Figure 4B), and the subgroup enrichment of mTOR signaling was validated in two independent cohorts ( Figure 4C), consistent with prior isolated reports in model systems 42,43,44 . To interrogate the potential effect of mTOR treatment on the prostate, we examined prostate size on cross-sectional imaging in patients taking mTOR inhibitors.…”
Section: Resultssupporting
confidence: 86%
“…These discrepancies may point to the need of targeting rapamycin-treatment to an animal model that already manifests metabolic dysregulation and aging phenotypes. Evidence supporting this hypothesis includes rapamycin treatment-related decrease in obesity and prevention of weight gain in rodents and humans [ 25 - 32 ] as well as downregulation of fasting levels of phosphorylated S6 (p-S6; a marker of mTORC1 activity) in mice on high-fat diet [ 33 , 34 ]. Given that high fasting levels of p-S6 is indicative of increased geroconversion from quiescence to senescence [ 35 , 36 ] and the suppression of geroconversion by rapamycin prevents age-related diseases in mammals [ 34 ], the observed beneficial effects on age-related declines in muscle strength and aerobic capacity among LCR rats exhibiting metabolic dysregulation may in fact result from rapamycin-induced suppression of “systemic hyper-functions (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism might be the blockade of mammalian target of rapamycin (mTOR)-dependent increase in HIF-1α and HIF-2α protein levels and VEGF upregulation. In addition, rapatar, a nanoformulation of rapamycin, has been demonstrated to decrease chemically-induced BPH in two rat models, without obvious side effects [ 32 ]. Moreover, increasing studies have demonstrated that rapamycin prolongs life span and prevents age-related diseases in mice [ 33 - 35 ].…”
Section: Discussionmentioning
confidence: 99%